Pemanfaatan Mikro Organisme Lokal (MOL) pada Pembuatan Pupuk Organik Cair (POC) dengan Memanfaatkan Limbah Sayuran - Irfan Ihza Wardana; Indri Purwaningsih; Pramesti Dewi; Dewi Mustikaningtyas (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to analyse the Nitrogen and pH levels of liquid organic fertiliser (LOF) made using microlocal organisms (LMO) based on vegetable waste. The method used was an experimental method through a fermentation process carried out at the Center for Standardisation and Industrial Pollution Prevention Services (BBSPJPPI). The results showed that the LOF produced had a Nitrogen content of 0.03% and a pH of 3, which did not meet the quality standards of liquid organic fertiliser in Indonesia, namely Nitrogen content of 2-6% and a neutral to slightly acidic pH (5-7). The low Nitrogen content is due to the Nitrogen-poor composition of the vegetable waste, while the overly acidic pH is due to the prolonged fermentation time, which triggers the formation of organic acid compounds. To improve the quality of LOF, optimisation is needed in the selection of raw materials, fermentation ratio, and control of fermentation parameters such as time and temperature. This research provides recommendations for the development of higher-quality LOFs that comply with national standards.